2021
DOI: 10.3390/ijms222111793
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies from Patients with Scleroderma Renal Crisis Promote PAR-1 Receptor Activation and IL-6 Production in Endothelial Cells

Abstract: Background. Scleroderma renal crisis (SRC) is a life-threatening complication of systemic sclerosis (SSc). Autoantibodies (Abs) against endothelial cell antigens have been implicated in SSc and SRC. However, their detailed roles remain poorly defined. Pro-inflammatory cytokine interleukin-6 (IL-6) has been found to be increased in SSc, but its role in SRC is unclear. Here, we aimed to determine how the autoantibodies from patients with SSc and SRC affect IL-6 secretion by micro-vascular endothelial cells (HMEC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 69 publications
0
19
1
Order By: Relevance
“…Our data reveal an association between ICU treatment in severe COVID-19 and generation of anti-PAR1 abs, which are associated with poor outcome. Intriguingly, we found no association between anti-PAR1 abs and systemic IL-6, despite the suggested agonistic role of anti-PAR1 abs on PAR1/p70S6K/ERK-dependent IL-6 expression in endothelial cells [13].…”
Section: Competing Interestscontrasting
confidence: 77%
“…Our data reveal an association between ICU treatment in severe COVID-19 and generation of anti-PAR1 abs, which are associated with poor outcome. Intriguingly, we found no association between anti-PAR1 abs and systemic IL-6, despite the suggested agonistic role of anti-PAR1 abs on PAR1/p70S6K/ERK-dependent IL-6 expression in endothelial cells [13].…”
Section: Competing Interestscontrasting
confidence: 77%
“…Further experiments revealed an increased transcriptional activity of c-FOS and AP-1 after stimulation with SSc–IgG, which finally results in IL-6 mRNA expression and, subsequently, secretion of IL-6. To sum this up, anti-PAR-1 autoantibodies resemble the signaling pathway of thrombin, one of the natural ligands, which also leads to IL-6 secretion after binding to PAR-1 [ 158 ]. However, currently, the role of IL-6 in scleroderma renal crisis is obscure.…”
Section: Which Autoantibodies Might Be Useful As Predictors Of Diseas...mentioning
confidence: 99%
“…IL-6 is one of the major cytokines produced by endothelial cells and inflammatory cells in sepsis, cytokine release syndrome associated with chimeric-antigen receptor T-cell therapy [ 40 ], and cytokine storm syndrome after COVID-19 infection [ 41 ]. Several experimental studies demonstrated IL-6 production by cultured endothelial cells after stimulation by LPS [ 42 ] and autoantibodies from patients with scleroderma renal crisis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%